Parents' perceptions of available support following diagnosis of childhood cancer at Kamuzu Central Hospital, Lilongwe,Malawi - Gundo, Beatrice (2021)
The purpose of this study was to explore parents' perception of available support following diagnosis of childhood cancer at Kamuzu Central Hospital, Lilongwe, Malawi. The study utilized descriptive design of quantitative research to achieve research objectives. Sixty participants participated in the study. Data were collected using a questionnaire developed by the researcher based on literature review. Statistical Package for the Social Science (SPSS) version 20 was used to analyze the data. Majority of the parents reported that there are nurses and doctors who care for their sick children. They also reported availability of information regarding children’s condition, treatment, food, spiritual support and accommodation if needed. The parents rated highly the availability of treatment (excellent, 68.4%, n=41). Majority of the parents reported that provision of accommodation was good (good, 85%, n=51) and that they are treated as an individual rather than a typical parent of cancer child (good, 100%, n=60). Parents also reported that children are not cared for holistically (e.g. mental, emotional and social needs) instead only their physical needs are met (81.7%, n=49) and all parents reported that there is poor provision of advice on how to get information or to contact other parents, organizations. In relation to treatment, parents reported poor explanation on treatment (70%, n=42), and on the types of cancer services available (80%, n=48). Majority of the parents reported that provision of spiritual support is good (76.7%, n=46) and there is adequate treatment at the facility (83.3%, n=50), however they are not provided with an opportunity to make decisions about treatment (71.7%, n=43).vi The study highlights areas of concern for practice, management, education and research relevant to paediatric oncology. Health professionals need to update themselves on peadiatric oncology through conducting research and attending research conferences on pediatric oncology. They also need to facilitate parents’ access to information and should be able to give timely, appropriate information.